Reservoirs of pathogenic Leptospira species in Uganda - Alinaitwe, Lordrick; Dürr, S.; Kankya, C.; Cook, Elizabeth A.J.; Mayer-Scholl, A. (2022)
Introduction: Leptospira are spirochete bacteria, including pathogenic species that cause leptospirosis, a zoonotic disease endemic in the tropics. In Uganda, Leptospira seroprevalence has been reported among outpatients at three hospitals, with human-animal interaction implicated as source of human Leptospira exposures. However, corresponding animal Leptospira infection has only been demonstrated in cattle, leaving the status in several potential reservoirs like other livestock species and environmental sources unknown. The current study aims at determining the occurrence, and risk factors for Leptospira infection among livestock species and environmental sources in Uganda.